Partial molecular volumes of cholesterol and phosphatidylcholine in mixed bilayers - Gallová J.; Želinská K.; Balgavý P. (European Pharmaceutical Journal, 2017)
Dispersion of multilamellar liposomes of dimyristoylphosphatidylcholine (DMPC) and cholesterol (CHOL) were studied by vibrational densitometer for the CHOL mole fractions X = 0−0.54 in the temperature range 18−50 °C, both below and above the main phase transition. DMPC-CHOL bilayers served as a simple model for lipidic part of biological membrane. Volumetric parameters are essential not only to evaluate the data obtained by scattering and diffraction methods on model membranes but can provide valuable information about molecular packing in bilayers and the phase behaviour of lipid-CHOL mixtures. In this paper, preliminary results regarding the changes in the specific volume of lipid bilayer with increasing temperature and CHOL content are presented. Different values of apparent molecular volume of CHOL for different CHOL mole fraction pointed out the non-ideal mixing of DMPC and CHOL.